A Standard Lipid Panel Is Insufficient for the Care of a Patient on a High-Fat, Low-Carbohydrate Ketogenic Diet - Norwitz, Nicholas G.; Loh, Vyvyane (Frontiers in Medicine, 2020)
High-fat, low-carbohydrate ketogenic diets have recently become popular for weight loss as well as for the treatment of numerous chronic diseases; however, the general medical community still expresses concern regarding the impact of high-fat diets on serum lipids and cardiovascular risk. Herein we report on young man who adopted a ketogenic diet to effectively treat his inflammatory bowel disease. Incidentally, changes in his serum lipids were noted which would be considered adverse by current standards. A more critical analysis of his lipid profile suggests that the changes he experienced may not be dangerous and may, at least with regards to several parameters, represent improvements. This case study demonstrates how the manner in which lipid panels are often reported and reviewed can lead to misleading conclusions and highlights that, at least in the care of those on a ketogenic diet, more nuanced analyses of lipid subfractionations should be conducted in order for physicians to provide optimal care and clinical recommendations.